Exploring the need for a kickstarter toolkit for special education educators to teach authoring and illustrating - Arumugam, Shyielathy; Mustafa, Mazlina Che; Abdullah, Norazilawati; Shamsudin, lylia Dayana; Mohd Jamil, Mohd Ridhuan; Dzainudin, Masayu (Institute of Advanced Engineering and Science, 2025)
This study examines the need for developing a Kickstarter toolkit designed to support special education teachers in teaching entrepreneurship through the creation of children’s storybooks. Entrepreneurship education is increasingly recognized as a valuable addition to special education, promoting skills such as creativity, problem-solving, and independence. A survey conducted among 170 special education teachers from the Kuala Kangsar district, selected through judgmental sampling, revealed strong support for introducing entrepreneurship education into special education curricula (M=3.69, SD=0.71). Teachers also emphasized the importance of employing pedagogical approaches to effectively teach entrepreneurship concepts (M=3.89, SD=0.69). Moreover, the findings indicate an urgent need for a dedicated toolkit to facilitate such activities, with educators expressing high levels of agreement regarding its necessity (M=3.99, SD=0.73). These results underscore the positive perception of special education teachers toward entrepreneurship education and the crucial role a specialized toolkit could play in equipping educators with the resources needed to foster entrepreneurial competencies in students with special needs.